Molecular characterization and differential expression studies of an oxidosqualene cyclase (OSC) gene of Brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Sonawane, Prashant; Singh, Somesh; Kumari, Uma; Ruby; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2013)
Triterpenoid saponins are the class of secondary metabolites, synthesized via isoprenoid pathway. Oxidosqualene cyclases (OSCs) catalyzes the cyclization of 2, 3-oxidosqualene to various triterpene skeletons, the first committed step in triterpenoid biosynthesis. A full-length oxidosqualene cyclase cDNA from Bacopa monniera (BmOSC) was isolated and characterized. The open reading frame (ORF) of BmOSC consists of 2,292 bp, encoding 764 amino acid residues with an apparent molecular mass of 87.62 kDa and theoretical pI 6.21. It contained four QxxxxxW motifs, one Asp-Cys-Thr-Ala-Glu (DCTAE) motif which is highly conserved among the triterpene synthases and another MWCYCR motif involved in the formation of triterpenoid skeletons. The deduced amino acid sequence of BmOSC shares 80.5 % & 71.8 % identity and 89.7 % & 83.5 % similarity with Olea europaea mixed amyrin synthase and Panax notoginseng dammarenediol synthase respectively. Phylogenetic analysis revealed that BmOSC is closely related with other plant OSCs. Quantitative real-time PCR (qRT-PCR) data showed that BmOSC is expressed in all tissues examined with higher expression in stem and leaves as compared to roots and floral parts.

Molecular cloning, biochemical characterization, and differential expression of an acetyl-CoA C-acetyltransferase gene (AACT) of brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Ruby; Singh, Somesh; Sonawane, Prashant D.; Srivastava, Sameer; Kumari, Uma; Kumar, R. J. Santosh; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Bacopa monniera (Brahmi) is an important Indian medicinal herb found in wet damp and marshy places. It produces medicinally important compounds known as bacosides along with alkaloids like brahmine and herpestine. Bacosides are triterpenoid saponins and their biosynthesis takes place via the isoprenoid pathway starting with acetyl-CoA. Acetyl-CoA C-acetyltransferase (AACT; EC 2.3.1.9), also known as acetoacetyl-CoA thiolase (Thiolase II), catalyzes the condensation of two acetyl-CoA to form 4-C compound acetoacetyl-CoA. Acetoacetyl-CoA is an important starting molecule for biosynthesis of various metabolites. Here, we report the cDNA cloning and characterization of acetyl-CoA C-acetyltransferase gene from B. monniera. The full-length gene was isolated using a RACE PCR protocol. The cDNA encoding AACT was designated as BmAACT (FJ947159) revealed an ORF of 1,218 bp and 405 amino acids, and shares 80 % similarity with other plant AACTs. Phylogenetic analysis showed that BmAACT is related closely to other dicot plants AACTs. The BmAACT gene was over-expressed in Escherichia coli as a 6X His-tag fusion protein and purified to homogeneity by Ni-NTA and gel filtration chromatography. Activity of recombinant protein was confirmed by thiolytic cleavage of acetoacetyl-CoA in the presence of 5 mM Mg2+, showing K (m) and V (max) of 20.67 mu M and 96.21 mu mol/min, respectively, with high catalytic efficiency (k (cat) = 2.30 x 10(5) min(-1)). Quantitative real-time PCR analysis showed that the expression of BmAACT is tissue-specific, and accumulation of transcripts is greater in roots and petals, followed by sepals, stem, leaf and pedicel.
Keywords: Acetyl-CoA C-acetyltransferase; Bacopa monniera; Isoprenoid pathway; Triterpenoid saponin